Psammolestes tertius Lent & Jurberg, 1965 (Hemiptera, Reduviidae, Triatominae): first report in Sergipe State, Brazil - Jader de Oliveira; João Aristeu da Rosa; Felipe Mendes Fontes; David Campos Andrade; Rubens Riscala Madi; Cláudia Moura de Melo (Revista da Sociedade Brasileira de Medicina Tropical, 2021)
Abstract INTRODUCTION: This study reports the first occurrence of Psammolestes tertius (Hemiptera, Reduviidae, Triatominae) in the state of Sergipe, Brazil. METHODS: In 2020, 95 specimens were collected from the municipality of Porto da Folha, Sergipe, Brazil. RESULTS: This finding expands the geographical distribution of the species from 15 states in Brazil to 16 and increases the biodiversity of triatomines in the state of Sergipe. CONCLUSIONS: The presence of P. tertius in the state of Sergipe demonstrated a wider distribution of this species in northeastern Brazil.